The potential of landscape metrics for estimating forest ﬁre risk in Poland - Kolanek, Aleksandra; Szymanowski, Mariusz; Niedzielski, Tomasz (Quaestiones Geographicae, 2026)
Although forest ﬁres are widely studied, few studies focus on the relationship between forest landscape structure and ﬁre events. This paper examines the signiﬁcance of differences in landscape metrics between buffer zones surrounding ﬁres and buffer zones surrounding randomly selected points. The objective of this comparison was to determine whether landscape characteristics are factors that may contribute to the occurrence of ﬁres. The analysis was based on ﬁres in 2015 in the Lubelskie Voivodeship, eastern Poland. Statistical evaluation involved the Ljung–Box test and the Mann–Whitney U test. The results indicate that areas surrounding the places of ﬁre occurrences exhibit greater fragmentation compared with the control groups, as reﬂected by smaller, more numerous and more irregularly shaped forest patches. While landscape-level analysis provides a broad overview, the class-level analysis helps to pinpoint which forest types and developmental stages are susceptible to these effects. These ﬁndings underscore the potential signiﬁcance of forest structure in shaping ﬁre risk in Poland.